2023
DOI: 10.1038/s41422-023-00783-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin protects against genotoxicity by promoting genome repair

Abstract: Dear Editor,Radiation sickness is a major health concern. 1 The quest for radiation countermeasures started in the wake of the devastation witnessed following the nuclear detonations during the Second World War and has continued through the subsequent radiological accidents around the world. A radioprotector is also required for prophylactic use by staff working at radiation sources, pilots, and astronauts at high risk of space radiation, or patients undertaking lengthy radiological procedures. Despite decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…As for WT mice, the apoV group showed higher survival rates (30‐day survival rate: 5/7) than the PBS group (30‐day survival rate: 2/7), along with prolonged survival time (Figure 4a), reduced weight loss (Figure 4b), decreased numbers of γH2AX foci in multiple organs (Figure 4c‐g) and improved 24‐h survival of bone marrow cells compared to the PBS group (Figure 4h). Among the tissues we examined, the bone marrow was the most severely damaged after irradiation (Jiang et al., 2023; Mettler & Voelz, 2002). We harvested bone marrow cells from a femur and tibia, lysed the red blood cells, and counted the total number of cells as previously described (Zhao et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As for WT mice, the apoV group showed higher survival rates (30‐day survival rate: 5/7) than the PBS group (30‐day survival rate: 2/7), along with prolonged survival time (Figure 4a), reduced weight loss (Figure 4b), decreased numbers of γH2AX foci in multiple organs (Figure 4c‐g) and improved 24‐h survival of bone marrow cells compared to the PBS group (Figure 4h). Among the tissues we examined, the bone marrow was the most severely damaged after irradiation (Jiang et al., 2023; Mettler & Voelz, 2002). We harvested bone marrow cells from a femur and tibia, lysed the red blood cells, and counted the total number of cells as previously described (Zhao et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear radiation poses a significant challenge to future society (Mettler & Voelz, 2002). However, to date, more attention has been given to drugs that inhibit DNA repair, and there has been limited research on effective DNA repair medications (Jiang et al., 2023). Although it has been suggested that some agents, such as aspirin, exhibit anti‐inflammatory and DNA repair effects in irradiation‐induced damage, clinically there is no effective therapeutic approach to treating irradiation‐induced DNA damage (Jiang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, aspirin intake may be protective against an increase in PIG-A mutation levels. Whilst the anti-cancer effects of aspirin have been well-documented (Jiang et al, 2023), the specific interaction of dietary intake and erythrocyte mutant levels remains unclear. Cancer treatment, that is, chemo or radiotherapy, may also change mutation levels.…”
Section: Pig-a Mutation Test In Human Biomonitoringmentioning
confidence: 99%